ChemInform Abstract: Highly Transparent BaAl4O7 Polycrystalline Ceramic Obtained by Full Crystallization from Glass. Issue 6 (20th February 2013) - Allix, Mathieu; Alahrache, Salaheddine; Fayon, Franck; Suchomel, Matthew; Porcher, Florence; Cardinal, Thierry; Matzen, Guy
Abstract A highly transparent polycrystalline BaAl4O7 ceramic is prepared by annealing a glass bead (obtained by melting a 1:2 molar mixture of BaCO3 and Al2O3 followed by rapid quenching) in an open‐air atmosphere tubular furnace at 1000—1100 °C for 2—24 h.